Overview Of Anemia In Young Women Low Body Mass Index (Thin Category): Gambaran Anemia Pada Remaja Putri Dengan Indeks Massa Tubuh Rendah (Kategori Kurus) - Risna’im, Annisa Rohmania; Mahtuti, Erni Yohani; Masyhur, Muhammad; Faisal (Universitas Muhammadiyah Sidoarjo, 2022)
In the period of growth and development, adolescents need more nutrients. Adolescents face many health problems due to biological and psychological changes as well as malnutrition. Anemia is a common health problem. Riskesdas data in 2018, in Indonesia there is a prevalence of anemia of 48.9%. Cases of anemia often occur in the age group of 15-24 years and 25-34 years. This study aims to determine the state of anemia with a lean body mass index in adolescent girls at SMK Madani Turen, Malang Regency. The research design used is descriptive quantitative with a cross sectional approach and a total of 101 respondents. The samples obtained had a lean body mass index of 24 people (23.76%) and the majority were known not to be anemic, namely 17 people (70.83%) and those who had anemia were 7 people (29.16%). The p value of the Fisher's exact test is 0.000 if the p value is <0.05, which means Ho is rejected, it can be concluded that there is a relationship between body mass index and Hb levels in female students at SMK Madani Turen.